Integrity Advisors and the Development of Administrative Communication Culture - Hohmann, Balázs J.D. (European Journal of Multidisciplinary Studies, 2019)
The integrity advisers are the central actors of integrity management systems of the administrative organizational structure, whose main task is to promote the implementation of the integrity approach within state administration institutions. As a complementary part of this task, we can separate the tasks of corruption prevention and the improvement of organizational integrity, of which the latter being discussed in more detail in this research and presentation. Integrity advisers play a key role in the development of organizational culture among public administration bodies, such as bodies exercising administrative authority. Looking at the topic more closely, with regard to the activities of integrity advisers, it can be clearly established that one of the engines of their operation is the proper and deep communication, which is not only necessary within the public administration and inter-agency transactions, but it also means communication activities that can be interpreted in the relationship between the public and clients. Equally important is their training and other activities aimed at developing staff awareness, relationships, situation assessment and action practices, which, in addition to and in part within public service training, provide an opportunity to shape organizational culture. The presentation and the paper aims to show the role of integrity advisors in developing organizational culture and transparency in the administration based on recent research experience about online presence of integrity advisors and in-depth interview surveys.
Keywords: administrative procedure, integrity advisor, organizational culture, transparency.